Maqasid al-shariah: suatu kajian terhadap ijtihad Ali ibn Abi Thalib - Eficandra, Eficandra (Sekolah Tinggi Agama Islam Negeri Salatiga, 2012)
Ijtihad conducted by Ali ibn Abi Talib continuously to understand in depth the purpose of Islamic law and reason for its implementation, and to realize maslahah (the public good) for human life on earth. This Ijtihad was always supported by nas the Qurâanâs and Sunnahâs text) and also according to the spirit of Shariâah. The results of Aliâs ijtihad if linked with the approach and application of maqasid al-shariâah (theÂ goals and objectives of Islamic law) as the study of usul al-fikih (the methodology of Islamic law) had many similarities. In another sense, Ali ibn Abi Talib was really smart to understand and apply maqasid al-shariâah in the five types of maslahah, namely faith or religion, life or human self, intellect, lineage or posterity, and property or wealth. Likewise, in the application of the five maslahah, levels and priorities in the form daruriyyat (the essential benefits), hajiyyat (the complementary benefits), and tahsiniyyat (the embellishment benefits) was always be considered by him. On the other hand, if there was a clash between one maslahah with another maslahah, Ali ibn Abi Talib solved it by consideration of the level and priority in the implementation of maslahah to be realized.